Hakikat Kepemimpinan Islam: Sinergi antara Integritas dan Perbaikan Sistem - Sari, Nirmala; Anwar Sidik (Moral : Jurnal kajian Pendidikan Islam, 2026)
Islamic leadership faces significant challenges related to personal integrity and institutional governance, requiring a comprehensive theoretical study to bridge these gaps. This research aims to examine the integration of prophetic values with system improvement to strengthen Islamic leadership in the modern context. The study employs a qualitative approach based on literature review and textual analysis, exploring Islamic leadership theories, public administration practices, and historical experiences of Islamic civilization. The findings indicate that Islamic leadership becomes more effective when the personal integrity of leaders is aligned with adaptive, transparent, and accountable institutional systems. These results emphasize that system improvement is necessary to ensure moral values are not limited to individual practice but embedded within organizational governance and social institutions. The study also highlights the relevance of Islamic leadership in addressing the era of disruption, where synergy between prophetic character and institutional reform is essential for sustainability. The research recommends emphasizing the synergy between moral values and system improvement so that Islamic leadership can sustainably address social challenges while remaining relevant to modern demands and contemporary societal needs.